THE ROLE OF IMMUNOSUPPRESSIVE THERAPY IN MANAGING AUTOIMMUNE DISEASES IN CATS AND DOGS (The Research of Medical Science Review, 2025)
Autoimmune diseases in cats and dogs pose significant therapeutic challenges due to their complex pathogenesis and varied clinical manifestations. This study investigates the efficacy, safety, and comparative outcomes of immunosuppressive therapies commonly used in veterinary practice. Through comprehensive analysis of recent literature and clinical data, we evaluated four major drug classes: glucocorticoids, calcineurin inhibitors, cytotoxic agents, and Janus kinase inhibitors. The findings demonstrate that glucocorticoids, particularly prednisone, are effective in rapidly controlling inflammation, though their prolonged use is limited by substantial side effects. Cytotoxic agents like azathioprine showed enhanced remission rates in combination therapies but require careful monitoring due to their toxicity profile. Thus, cyclosporine provided the desired effect of immunosuppression selectively with fewer side effects in the long-term maintenance phase. Amongst them newly developed Janus kinase inhibitors were proven quite effective in terms of immune modulation with better owner assigned quality of life scores. Combinations were seen to provide the greatest incremental improvement in clinical benefit, up to 70%, and significanly prolonging survival time, although at the risk of more side effects. Table and figures showed trends in treatment response, survival of patients, cost and the number of patients who relapsed stressing on the fact that the treatment regimes should be tailored. Despite improvements, monotherapies produced poor efficacy for relapse and the results were species dependent. This paper identifies and discusses the option of using tailored, multimodal immunosuppressive protocols as the optimal approach when treating autoimmune diseases in companion animals while maintaining efficacy, safety, and quality of life. In future research, the emphasis should be put into precision immunotherapy as well as the application of innovative technologies including personalized vaccine and CAR T-cell therapies.